ANALISIS KARAKTERISTIK PEKERJAAN TERHADAP KINERJA DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL INTERVENING - Purnawan, Putu Eka Wati; Cahyono, 2Dwi; Herlambang, 3Toni (Jurnal Sains Manajemen dan Bisnis Indonesia, 2017)
ABSTRACTThe purpose of this research is to know the analysis of job characteristics on performance with organizational culture as intervening variable on the employees at Mangli Puskesmas Jember District. This research is a quantitative research with survey approach. Total population and sample of 30 employees. With the formulation of the problem is how to improve the performance of employees for effectiveness in improving the quality of performance through job characteristics variable to the performance of employees through organizational culture as intervening variables can be met immediately by employees of Mangli Puskesmas. The analytical technique used is the path analysis with the results of research indicates that the characteristics of the work have a significant effect on the results of research indicate that the characteristics of the work have a significant effect on organizational culture, job characteristics significantly influence employee performance, organizational culture significantly affect employee performance and job characteristics significantly performance of employees through organizational culture. While the influence of independent variable to dependent variable in this research is 77,7%.Keywords: Job Characteristics, Organizational Culture and Employee Performance